Conceptualising China through translation - St. André, James (Alternative sinology., 2023)
This book provides an innovative methodology for investigating how China has been conceptualised historically, tracing the development of four key concepts (filial piety, face, fengshui, and guanxi) in English and Chinese. It explores how specific ideas about the uniqueness of Chinese culture influence the ways we think about China.